Determinants of health-seeking behaviour in rural district of Jasikan, Ghana: a cross-sectional study - Courage Edem Ketor; Juliet McDonnell; Charles Kwaku Benneh; Emmanuel Sarkodie; Isaac Annobil; Fidelis Atia; Adelaide Mensah; Samuel Owusu Somuah; Selorm Akakpo (BMC, 2024)
Abstract Background The Ghana Health Service aims to ensure the health of all Ghanaians. Understanding the factors that influence people's health-seeking behaviour will help the Ghana Health Service evaluate and enact policies that will enable it to achieve set targets. This research aimed to determine the factors that influence the health-seeking behaviour of the residents of Jasikan District and ascertain the importance of the well-being clinic in this context. Methods The study design was a community-based cross-sectional study using a mixed method of data collection. A stratified sample of 295 respondents from the five [5] sub-districts of the target population was obtained. Cramer's V statistic was used to assess the effect size and significance of the association between categorical variables. Further, multiple binary logistic regression was used to determine significant predictors of health-seeking behaviour. Health seeking behaviour was categorised as appropriate or inappropriate. The health seeking behaviour of participants was considered appropriate if they sought health care at public health facilities, private health facilities, and licensed Pharmacies/OTCMS and inappropriate when participants sough care at traditional/faith healers, engaging in self-medication, and not taking action during an illness episode. Results The mean age of participants in the study was 37.49 ± 15.74 years. Females comprised the majority of study respondents (160; 56.3%). When they fell ill, 61% of respondents chose formal public health institutions as the first port of call. A significant proportion of respondents (245; 83%) preferred appropriate health-seeking behaviour, with age (p = 0.045) and health insurance status (p < 0.01) significantly influencing where respondents sought care. More than half of respondents indicated that affordable service (59.9%), readily available drugs (54.5%), and good services (52.0%) are key characteristics of respondents' preference for service in healthcare. The educational level significantly correlated with service characteristics when people seek health care (p = 0.035). The severity of illness (9; 28.1%), perception of a facility as the best place (7; 21.9%), well-trained staff (4; 12.5%), and professionalism (3; 9.4%) influenced respondents' choice of health care. More than half (78%) of respondents agreed with the need for a well-being clinic in a hospital. The binary logistic regression indicates that religion is a significant predictor the appropriateness of participants' health seeking behaviour, but the overall model could not improve the overall prediction rate of the constant model. Conclusion The health-seeking behaviour of the people of Jasikan is good. The participants' sex, good service, affordability, and availability of medicines are critical service characteristics that influence the choice of healthcare providers. Managers of health facilities should consider these characteristics to remain competitive and drive positive health-seeking behaviour in the community. Facilities are encouraged to set up a functional well-being clinic and open it to the public.